Work Engagement pada Karyawan di DKI Jakarta: Pengaruh Collaboration Skills, Digital Leadership, dan Perceived Organizational Support - Karina Rizky; Putri Ramadhani; Rauzatul Husnia; Nopriadi Saputra (Penerbit Goodwood, 2021)
Purpose: This research is to examine the effect of collaboration skills on work engagement, digital leadership on work engagement, perceived organizational support on work engagement, and collaboration skills, digital leadership, and perceived organizational support (simultaneously) on employees in DKI Jakarta. Research Methodology: This study used descriptive research methods and data collection techniques. Questionnaires were distributed to 388 DKI Jakarta employees. The analytical method used was descriptive analysis, validity test, reliability test, correlation test, difference test, and hypothesis testing. Results: The results of this study indicate that collaboration skills have a significant effect on work engagement, digital leadership has a significant effect on work engagement, digital leadership has a significant influence on collaboration skills, perceived organizational support has a significant effect on work engagement, perceived organizational support has a significant influence on collaboration skills, and perceived organizational support has a significant influence on digital leadership for employees in DKI Jakarta. Limitations: This study only assesses the variables of work engagement, collaboration skills, digital leadership, and perceived organizational support, and only employees who work in DKI Jakarta, as well as the limited literacy on collaboration skills and digital leadership. Contribution: It can be used as a reference in developing company strategies in increasing work engagement, and as a means of increasing knowledge about work engagement, collaboration skills, digital leadership, and perceived organizational support.